Magiens dæmonsprog - introduktion til S. J. Tambiah - Øjvind Jørgensen (Religionsvidenskabeligt Tidsskrift, 1996)
The article is an introduction to the anthropologist S. J. Tambiah and his theory on magic. Dissociating himself from the evolutionists (ie.e J. G. Frazer) and the functionalists (i.e., B. Malinowski) aand their attempts to place "magic" more or less within the framework of "causality", Tambiah focuses on the fact that in the actions human beings are simultaneously involved in two modalities, sc. the modality of causality and the modality of performative acts. He combines Sausurrean structural linguistics with the theory of performative speeech acts as developed from J. L. Austin and paalies this combination on cases taken from Evans-Pritchard's Azande studies. By doing so, the brings about a new and more fruitful understanding of magic. Finally, on the basis of Tambiah's thoughts I propose a definition of magic which goes beyond the traditional, scientifically inspired perception of causaliity.